An Approach for All in Pharmacy Informatics Education - Fox, Brent I.; Flynn, Allen; Clauson, Kevin A.; Seaton, Terry L.; Breeden, Elizabeth (American journal of pharmaceutical education, 2017)
Computerization is transforming health care. All clinicians are users of health information technology (HIT). Understanding fundamental principles of informatics, the field focused on information needs and uses, is essential if HIT is going to support improved patient outcomes. Informatics education for clinicians is a national priority. Additionally, some informatics experts are needed to bring about innovations in HIT. A common approach to pharmacy informatics education has been slow to develop. Meanwhile, accreditation standards for informatics in pharmacy education continue to evolve. A gap remains in the implementation of informatics education for all pharmacy students and it is unclear what expert informatics training should cover. In this article, we propose the first of two complementary approaches to informatics education in pharmacy: to incorporate fundamental informatics education into pharmacy curricula for all students. The second approach, to train those students interested in becoming informatics experts to design, develop, implement, and evaluate HIT, will be presented in a subsequent issue of the Journal.